Treatment of fractures of the distal radius and ulna in toy breed dogs with circular external skeletal fixation: a retrospective study - Piras, L.; Cappellari, F.; Peirone, B.; Ferretti, A. (Veterinary and Comparative Orthopaedics and Traumatology, 2011)
Objective: To evaluate the effectiveness of circular external skeletal fixation (CESF) in treating fractures of the distal radius and ulna in toy breed dogs, and to document the type and frequency of complications associated with this technique.Methods: The medical records of small breed dogs with fractures of the distal radius and ulna admitted to the University of Turin and to the Clinica Ferretti between 2002 and 2009 were retrospectively reviewed. The criteria for inclusion of cases in the study were: body weight of 5 kg or less, transverse or short oblique fracture of the distal third of the radius and ulna, no previous repair attempts, and treatment with CESF as the sole method of fixation.Results: Twenty fractures in 16 dogs satisfied the criteria for inclusion into this study. No signs of infection or failure of fixation were detected in any case. Mean frontal plane alignment was 4.7° ± 2.7° and mean sagittal plane alignment was 12.7° ± 7.2°. Postoperative complications occurred in one patient. All fractures achieved union. Mean time until radiographic evidence of a bridging callus and subsequent implant removal was 71 days (range: 30–120).Conclusions: The results of this study support the use of CESF for treatment of fractures of the distal radius and ulna in toy breed dogs as an alternative to other methods of fracture fixation. However, this technique requires a series of follow-up examinations to evaluate the stability of the apparatus, the soundness of the wires and to determine the appropriate time for implant removal.
Keywords: Radius; fracture; circular external skeletal fixation; dog